The problem of dating fractures: A retrospective observational study of radiologic features of fracture healing in adults. (December 2021) - Viero, Alessia; Obertová, Zuzana; Cappella, Annalisa; Messina, Carmelo; Sconfienza, Luca Maria; Sardanelli, Francesco; Tritella, Stefania; Montisci, Massimo; Gregori, Dario; Tagliaro, Franco; Cattaneo, Cristina
Abstract: Accurate dating of bone fractures can be crucial in the context of forensic trauma analysis since it may provide essential information for the corroboration or contradiction of statements by victims or suspects in cases of domestic abuse or torture. The different stages of bone healing have been well described in the existing literature, and some previous studies attempted to define related timelines particularly in the paediatric population. However, the bone healing process can be very variable and despite the importance of the topic in the forensic field, so far little is known about the radiological appearance of bone fractures at different healing stages, and how this correlates with time, especially in an adult population. The aim of this retrospective observational study was to describe the temporal aspect of pre-defined healing stages as they appear on radiographs of tubular bone fractures in adults, and explore the effect of potential cofounding variables. A dynamic nomogram was developed as a user-friendly tool to be eventually applied in clinical or medico-legal settings. This study showed that the posttraumatic time interval (PTTI) increased progressively with the pre-defined healing stages. However, confounding factors, such as patients' age, sex, and location of the fracture need to be accounted for in the final estimation model. Further studies are needed to explore more potentially confounding variables to refine the presented outcomes. Better knowledge of the effect of different confounding variables in the dating of fracture healing will contribute to greater accuracy of PTTI estimation of bone fractures in adults. Highlights: Radiological appearance of fractures at pre-defined healing stages was studied in adults. Assessment of the posttraumatic time interval (PTTI) is essential for forensic evaluation of victims of violence. Mean and minimum PTTI of the occurrence of healing stages were identified. A dynamic nomogram for predicting the PTTI based on radiographic signs was created. Confounding variables, such as age, sex, location of trauma were accounted for in the model.